Fiber Reinforced High Volume Fly Ash Concrete for Rigid Pavement (International Journal of Innovative Research in Computer Science & Technology, 2022)
The most popular man-made construction  material in use today is concrete. It is made by combining  cementitious ingredients, water, aggregate, and occasionally  admixtures, in the proper ratios. Fresh concrete, also  referred to as plastic concrete, is newly mixed material that  may be moulded into any shape before hardening into the  substance known as concrete. A long-lasting chemical  interaction between water and cement causes the hardening,  which makes concrete stronger over time. The practicality,  beauty, and durability of concrete structures built during the  first half of the 20th century with plain round mild steel bars  and ordinary portland cement (OPC), as well as the ease of  obtaining the constituent materials (whatever their  qualities), contributed to the widespread use of concrete.
Keywords: Compressive Strength; Fiber Reinforced; Strength; Stabilization